2022
DOI: 10.3390/children9040464
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Temporal Meta-Analysis of Changes in Left-Behind Children’s Mental Health in China

Abstract: A considerable body of research using the Mental Health Test (MHT) has explored the psychological repercussions of the physical separation of children from one or both parents as they pursue better economic prospects in cities. Generally, these studies compare the mental health status (MHS) between left-behind children (LBC) and non-left-behind children (NLBC). That notwithstanding, little is known about the real policy impact of these studies on the ground over the years. Using a relevant search strategy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…For example, better employment in urban areas usually increases a family's income [4], but long-term parental migration adversely affects parent-child relationships, which may negatively impact the family's well-being [5]. Numerous studies have shown that compared with non-left-behind children (NLBC), LBC have higher risks for physical and mental health issues [6][7][8]. For example, a systematic review revealed that LBC had a higher prevalence of anemia and stunting than NLBC [9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, better employment in urban areas usually increases a family's income [4], but long-term parental migration adversely affects parent-child relationships, which may negatively impact the family's well-being [5]. Numerous studies have shown that compared with non-left-behind children (NLBC), LBC have higher risks for physical and mental health issues [6][7][8]. For example, a systematic review revealed that LBC had a higher prevalence of anemia and stunting than NLBC [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies consistently indicated that growing up without parental care and supervision is associated with a number of physical, mental, educational and social problems. Global evidences have depicted that children who lost their parents in their childhood experienced mental health problems (Gao et al, 2022;Misra et al, 2019;Wu et al, 2021;Zhang et al, 2022), retarded growth (Tian et al, 2017), elevated risk of mortality (Hiyoshi et al, 2021), poor academic performance and attainments (Cas et al, 2014; Kailaheimo-Lönnqvist & Kotimäki, 2020), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, studies have shown that LBC are more likely to have poor lifestyles, including internet addiction [10], smoking [11], excessive drinking [12], and skipping breakfast [13], compared with non-left-behind-children (NLBC). LBC are also at risk of suffering from various psychological problems [14][15][16],…”
Section: Introductionmentioning
confidence: 99%